Characteristics of Brillouin Fiber Laser Under Two Different Techniques - Mudhafer. H. Ali; Mohammed A. Saleh; Ali H. Abdulhadi (Journal of Madenat Alelem University College, 2019)
The effect of recycling transmitted Brillouin power (RTBP) ratio on the threshold of the single wavelength Brillouin fiber laser (SWBFL) utilizing a recycling technique (R-Technique) is investigated. Different single mode fiber (SMF) lengths are used as a gain medium for the proposed laser. The RTBP ratio is increased from 20 % to 100 % a steps of 20 %  and compared within the conventional technique (C-Technique) for each gain medium length. The laser threshold within R-Technique is enhanced by 48.4 % for gain medium length of 5 km and by 28.29 % for gain medium length of 30 km as compared within the C-Technique. This reduction in the threshold ratio is attributed to the fact that at long SMF (>10 km) the effective gain medium length tends to be approximately constant.